Meteorology and Atmospheric Physics - Meteorology and Atmospheric Physics (Springer Nature, 2026)
Meteorology and Atmospheric Physics publishes original research papers discussing physical and chemical processes in both clear and cloudy atmospheres. Discusses atmospheric dynamics and general circulation, synoptic meteorology, and more. Focuses on weather systems in specific regions such as the tropics, the polar caps, and the oceans. Emphasizes on atmospheric energetics, numerical modeling, and forecasting. Includes mathematical and statistical techniques applied to meteorological data sets.
FI 0.5
Q3
Keywords: Earth; Space & Environmental Sciences; Atmospheric Sciences; Ciencias atmosféricas; Acuerdos transformativos; Transformative agreements; Meteorología y física de la atmósfera; Dinámica atmosférica, modelización numérica y pronóstico; Procesos físicos y químicos, microfísica de nubes y eventos meteorológicos extremos